On Plastic Design of Rotating Complex Machine Elements - Zowczak, W. (Engineering Transactions, 1992)
The differential relations (analoguous to Henecky equations) along slip-lines in the presence of body forces are formulated. These relations may be used in constructing stress fields for plastic design of various machine elements undergoing large body forces. A slip-line net is constructed for the case of a strip loaded by tension and centrifugal forces. Application of this solution to plastic design of a rotor is demonstrated.